Assessing the mechanical and physical strength of banana pseudostem fiber and coconut coir as a fiber base for fiber-cement boards - Cortes, Alexandrea Clare D.; Puso, Mark NdSY L. (2019)
The purpose of this study was to create a natural fiber-cement board using a mixture of banana pseudostem fiber and coconut coir fiber as the fiber base, and to measure their physical and mechanical properties. Samples were created using different ratios of banana and coconut fibers as well as different ratios of the combined fibers and the cement slurry base. The sample boards were then tested to measure dimension tolerances, finished weight, density, compressive strength, impact strength, moisture content, water tightness and water absorption. The test results were then compared to two commercially available fiber cement boards (FCB) as well as benchmarked using the ASTM standards. Post-test it was discovered that the natural fiber cement boards were more lightweight than the FCBs found in the market as well as having less moisture content and water absorption. One out of the fifteen sample types passed the minimum flexural strength requirement and only five out of the fifteen passed the water tightness test. The study concludes that the created natural fiber cement boards were not a viable alternative building material in their current state.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2019